Pengaruh Adopsi Teknologi Digital dan Orientasi Pelanggan terhadap Kinerja Finansial: Studi pada UMKM di Kota Palopo - Lukmansyah Lukmansyah; Pemilia Sulistyowati (LPPM Politeknik Pratama, 2026)
This study examines the effects of digital technology adoption and customer orientation on the financial performance of micro, small, and medium enterprises (MSMEs) in Palopo City. The study responds to an empirical gap in which previous research has frequently examined both constructs separately, prioritized marketing performance over financial outcomes, or concentrated on regions with more established digital ecosystems. Using an explanatory quantitative design, data were collected from 100 MSME owners selected through purposive sampling and analyzed with Structural Equation Modeling-Partial Least Squares. The measurement model satisfied the required validity and reliability criteria. The structural model shows that digital technology adoption has a positive and significant effect on financial performance (β = 0.341; t = 5.094; p < 0.001), while customer orientation also has a positive and significant effect (β = 0.413; t = 5.933; p < 0.001). The R² value of 0.286 indicates moderate explanatory power, and the Q² value of 0.168 confirms predictive relevance. The principal contribution of this study lies in demonstrating that, within MSMEs operating in a medium-sized city, customer orientation exerts a stronger effect than digital technology adoption in explaining financial performance. These findings imply that strengthening MSME competitiveness requires not only digital capability but also the sustained ability to understand and respond to customer needs.